2016
DOI: 10.1016/j.jcm.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Distraction Spinal Manipulation on Postsurgical Continued Low Back and Radicular Pain Patients: A Retrospective Case Series

Abstract: Purpose: The purpose of this case series is to report on changes in pain levels experienced by 69 postsurgical continued pain patients who received Cox Technic Flexion Distraction (CTFD). Methods: Fifteen doctors of chiropractic collected retrospective data from the records of the postsurgical continued pain patients seen in their clinic from February to July 2012 who were treated with CTFD, which is a type of chiropractic distraction spinal manipulation. Informed consent was obtained from all patients who met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
(32 reference statements)
1
15
4
Order By: Relevance
“…The management strategies and intervention techniques commonly chosen as always or frequently included healthy lifestyle advice, pain education, exercise prescription, "non-thrust" manual therapies, and away from manipulative therapy, particularly with regard to the fused lumbar region. Distraction manipulation and mobilization were among the most commonly described manual treatments [26]. This differed somewhat from a survey of chiropractic treatments by Clijsters et al which identified the preferred treatments for lumbar conditions for patients without prior surgery as diversified (thrust) manipulation, followed by drop-table assisted and instrument-assisted manipulative techniques [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management strategies and intervention techniques commonly chosen as always or frequently included healthy lifestyle advice, pain education, exercise prescription, "non-thrust" manual therapies, and away from manipulative therapy, particularly with regard to the fused lumbar region. Distraction manipulation and mobilization were among the most commonly described manual treatments [26]. This differed somewhat from a survey of chiropractic treatments by Clijsters et al which identified the preferred treatments for lumbar conditions for patients without prior surgery as diversified (thrust) manipulation, followed by drop-table assisted and instrument-assisted manipulative techniques [46].…”
Section: Discussionmentioning
confidence: 99%
“…The reported point prevalence of postsurgical patients in US chiropractic clinics ranges from 2.3-12% [18][19][20]. Several case reports describe clinical improvements with chiropractic care in patients with postsurgical lumbar spine pain [21][22][23][24][25][26][27]. There are no cohort studies or experimental designs reporting on the outcomes of care provided by chiropractors in patients with prior lumbar fusion [28].…”
Section: Introductionmentioning
confidence: 99%
“…In a case report the author concludes that chiropractic treatment may be an effective means of treating pelvic disorders secondary to lower sacral nerve root compression [15]. In another study Cox et al, found that greater than 50% pain relief following chiropractic distraction spinal manipulation was seen in 81% of postsurgical patients receiving a mean of 11 visits over a 49-day period of active care [16].…”
Section: Methods and Frequencymentioning
confidence: 99%
“…There was a large body of lower-level studies that were not assessed for quality. This included 1 scoping review [31], 1 narrative review [32], 14 case series [33][34][35][36][37][38][39][40][41][42][43][44][45][46], 23 case reports , and 2 commentaries [70,71]. Ten of the case reports described 53 cases following discectomy, 16 reports described MMT in 143 cases post-laminectomy, 16 reports described MMT care for 67 cases after fusion, 1 report discussed post-surgical treatment in 8 cases after artificial disc replacement, and 1 report discussed care in 3 cases following implantation of spinal cord stimulators.…”
Section: Literature Reviews Case Reports and Commentariesmentioning
confidence: 99%
“…All but one intraoperative report [34] involved care provided by chiropractors. Favorable responses were reported with spinal manipulation [33,37,51,59], FD manipulation [38,41,51,52], manual therapy [52,56], and manipulation under anesthesia of the sciatic nerve [34] or spinal joints [36]. Following discectomy, a scoping review suggested early passive and active hip and knee flexion exercises to reduce time to independent mobility and return-to-work [31].…”
Section: Discectomymentioning
confidence: 99%